The Digital Nexus: Identity, Agency, and Political Engagement http://www.aupress.ca/index.php/books/120253 - Edited by Raphael Foshay (Cultural Dialectics, 2016)
Over half a century ago, in The Gutenberg Galaxy (1962), Marshall McLuhan noted that the overlap of traditional print and new electronic media like radio and television produced widespread upheaval in personal and public life: Even without collision, such co-existence of technologies and awareness brings trauma and tension to every living person. Our most ordinary and conventional attitudes seem suddenly twisted into gargoyles and grotesques. Familiar institutions and associations seem at times menacing and malignant. These multiple transformations, which are the normal consequence of introducing new media into any society whatever, need special study. The trauma and tension in the daily lives of citizens as described here by McLuhan was only intensified by the arrival of digital media and the Web in the following decades. The rapidly evolving digital realm held a powerful promise for creative and constructive good-a promise so alluring that much of the inquiry into this new environment focused on its potential rather than its profound impact on every sphere of civic, commercial, and private life. The totalizing scope of the combined effects of computerization and the worldwide network are the subject of the essays in The Digital Nexus, a volume that responds to McLuhan's request for a "special study" of the tsunami-like transformation of the communication landscape. These critical excursions provide analysis of and insight into the way new media technologies change the workings of social engagement for personal expression, social interaction, and political engagement. The contributors investigate the terms and conditions under which our digital society is unfolding and provide compelling arguments for the need to develop an accurate grasp of the architecture of the Web and the challenges that ubiquitous connectivity undoubtedly delivers to both public and private life.